Comparative effects of Curcuma longa and curcumin on paraquat-induced systemic and lung oxidative stress and inflammation in rats - Seyedeh Zahra Ghasemi; Arghavan Memarzia; Sepideh Behrouz; Zahra Gholamnezhad; Mohammad Hossein Boskabady (Mashhad University of Medical Sciences, 2022)
Objective: Comparative effect of Curcuma longa (C. longa) ethanolic extract and curcumin on paraquat (PQ)-induced systemic and lung oxidative stress and inflammation were evaluated in the present study.Materials and Methods: Control animals were exposed to normal saline and PQ group to 54 mg/m3 PQ aerosols (8 times, each time for 30 min). Treatment groups were exposed to PQ and treated with 150 and 600 mg/kg/day C. longa, or 30 and 120 mg/kg/day curcumin after PQ exposure period for 16 days. Total and differential white blood cells (WBC) and oxidative markers were measured both in bronchoalveolar lavage (BALF) and blood at the end of the study.Results: Total and differential WBC counts as well as malondialdehyde (MDA) level were significantly increased but total thiol content and the activities of catalase (CAT) and superoxide dismutase (SOD) were reduced in both the BALF and blood of the PQ group in comparison with the control group (p<0.05 to p<0.001). Both doses of C. longa and curcumin diminished MDA level, total and differential WBC counts in the blood and BALF but increased CAT and SOD activities in both of them compared to PQ group (p<0.05 to p<0.001). The effects of C. longa and curcumin high dose on most variables were markedly more than low dose (p<0.05 to p<0.001). Furthermore, the effects of curcumin on some variables were markedly more than C. longa (p<0.05 to p<0.001).Conclusion: Both C. longa and curcumin improved PQ-induced systemic and lung inflammation and oxidative stress, but the effect of curcumin was more prominent.